Pembaharuan Hukum Perjanjian Perkawinan Dan Akibat Hukumnya Terhadap Harta Dalam Perkawinan - Murniati, Rilda (JATISWARA, 2018)
Every marriage will give birth the union of assets that can be obtained by husband and wife during the marriage if not excluded by the marriage agreement. However, the Marriage Law explicitly and clearly stipulates that the marriage agreement must be made before the marriage takes place or at the time the marriage takes place. The existence of these legal provisions, in fact, is not entirely known by every prospective husband and wife and raises new problems related to land law that limits ownership rights to land and buildings for Indonesian citizens who marry other citizens without marriage agreements. This is the reason for the birth of a material test suit against the provisions of the Marriage Law contained in the Decision of the Constitutional Court No. 69 / PUU-XII / 2015. This decision forms the basis and legal basis for new arrangements as a source of legal renewal on the procedures for marriage agreements and their legal consequences for joint assets acquired in marriage. The born of legal renewal is the marriage agreement that can be made any time during the marriage in the form of an authentic deed at the notary and can be retroactive from the date the marriage takes place as long as the husband and wife agree and bind as a law to the parties. For this reason, the legal consequences of the legal status of joint assets acquired during marriage are the personal property of each husband and wife and their contents are binding on third parties as long as the third party has an interest.